Analisis Penerapan SAK EMKM Sebagai Dasar Penyusunan Laporan Keuangan Pada UMKM Sambal Mama’ Aji - Dewi Fatimah; Masnawaty Sangkala; Samsinar (Asosiasi Dosen Akuntansi Indonesia, 2026)
This study aims to analyze the application of the Financial Accounting Standards for Micro, Small, and Medium Entities (SAK EMKM) as a basis for preparing financial reports at the Sambal Mama'Aji MSME in Bulukumba Regency. A qualitative descriptive approach was used with data collection techniques through observation, interviews, and documentation. The results show that the Sambal Mama'Aji MSME has begun to apply the principles of SAK EMKM although still using manual recording methods. The separation between business and personal finances has been carried out well, and there is awareness among the owners of the importance of accountable and structured financial reports. However, limitations in technology and human resources are still found, which pose challenges in the full implementation of these accounting standards. The implementation of SAK EMKM has been significantly beneficial in increasing the transparency and professionalism of MSME financial management.